Medical device for rehabilitation after proximal femur fracture: usability study - Lages Domingues, Daniela de Jesus (2023)
Background: the Proximal Femur Fracture (PFF) is a serious public health concern, and the ABLEFIT Medical Device (MD) may be an added asset in the patient’s process of rehabilitation after PFF. Objectives:  to assess usability and ergonomics of the ABLEFIT for patient rehabilitation after PFF. Methodology: a descriptive observational study, using a mixed methodology, with data sourcing through two focus groups and usability questionnaire. Focus groups made up of eight participants each, one group with end users and one with Nurses Specialized in Rehabilitation Nursing (NSRN). All ethical principals were met. The quantitative data were analyzed using the Statistical Package for the Social Sciences (SPSS) v25 software, in addition to content analysis technique for focus groups. Results: the descriptive analysis of the quantitative data shows a positive appreciation, with higher scores in group A. Overall, participants considered the device to be useful for patient rehabilitation after PFF. Some group B participants perceived the learning process and usability of the medical device as complex. Conclusion: this study allowed to assess usability and improvement of the ABLEFIT for patient rehabilitation after PFF, and to contribute to better quality in Rehabilitation Nursing care services.